The Development of Management Model to Improve the Student Care and Support System Through the Quality Management Processes of the Special Education Center in Udon Thani Province - Saksaen, Niphaporn (Academic MCU Buriram Journal, 2025)
The purposes of this research were: 1) to study the current situation and needs for a management model of the student care and support system through the quality management processes of the Special Education Center in Udon Thani Province, 2) to develop a management model for the student support system through the quality management processes of the Special Education Center in Udon Thani Province, 3) to study the effects of implementing the management model for the student support system through the quality management processes of the Special Education Center in Udon Thani Province, and 4) to evaluate the implementation of the management model for the student support system through the quality management processes of the Special Education Center in Udon Thani Province. The sample group consist of 168 school administrators, teacher, patents, and the board of basic education. The research tools used in the data collection were structured interview questionnaire, five-level scale questionnaire with a reliability coefficient of 0.95 and the evaluation form of appropriateness, feasibility, and utility. Statistics used to analyze data include frequency, percentage, average, standard deviation. The research result found that: 1. The current situations of the student care and support system model have been found that the student care and support system face several problems. Data management is disorganized, there is a lack of specialized personnel development, and there are limitations regarding cooperation from parents and the community. There is also a shortage of resources, restricted coordination with external agencies that has not yet been effective. The needs for a student care and support system have been found that there is a need for a clear administrative model, practical tools and guidelines, as well as training to enhance skills. There is a need for a quality and transparent care system, with regular communication, in line with educational standards. 2. The results of developing the student support and support system model through the quality management process of the Special Education Center in Udon Thani Province resulted in the UD Care Model for managing the student care and support system. 3. The results of implementing the management model for the student support and assistance system through the quality management process of the Special Education Center in Udon Thani Province indicated that, overall, the average score was at a high level. 4. The evaluation results of the implementation of the management model indicated that the opinions of school administrators, school board members, teachers, and parents regarding the feasibility and usefulness of the management model through quality management processes to develop the student care and support system of the Special Education Center in Udon Thani Province were, overall, at a high level.